Nagari Government's Efforts to Develop Religious Activities through Community Organizations - Irma Sari; Reni Susanti; Beni Putra Hanafi (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2023)
The main problem in this thesis is the decline in religious activities in Nagari Salayo Tanang Bukit Sileh, this is caused by several factors such as the lack of role of the nagari government in providing assistance to community related to religious activities, the lack of prayer congregations in mosques or prayer rooms, where people die is more likely to be old people or certain people inside the care of the body starts from cutting the shroud, washing the body, accompanies, prays for and buries the body, when praying for the body using mosques or prayer rooms, the influence of technology such as cellphones or cellphones which gives addiction to its users. The type of research that the author uses is Field Research or field research. The data collection techniques that the author uses are through interviews and documentation. Data management is carried out descriptively qualitatively, then described and classified aspects of the problem contained in the research and explained in effective sentences. Based on the research that the author has conducted in Nagari Salayo Tanang Bukit Sileh, it can be concluded that, the efforts of the Government of Nagari Salayo Tanang Bukit Sileh in developing religious activities through community organizations (case study in Nagari Salayo Tanang Bukit Sileh) involve Nagari elements such as Alim Ulama, Niniak Mamak , Cadiak Pandai and Community Figure. There are other strategies implemented by the Nagari Salayo Tanang Bukit Sileh Government, such as; providing incentives to MDA teachers, Mosque Imams and Gharim, organizing funeral services and training mosque imams. The religious programs at LPTQ are the development of religious activities such as the practice of holding corpses, sermon training, mentoring for MDA teachers, Gharim and mosque imams, training for preachers.